Gender distinctiveness, communicative competence, and the problem of gender judgments in computer-mediated communication - Sierpe, Eino (Computers in Human Behavior, 2005)
Despite persistent claims regarding the ability of text-based computer-mediated communication to neutralize gender identities, few researchers have worked on the problem of gender distinctiveness in textual production and interpretation, gender judgments, and more importantly, the role of gender in the process of impression formation in electronic communication. Against this background, the author addresses the theoretical aspects of gender in textual communication and places the problem of gender distinctiveness and gender judgments in CIVIC in the context of Hymes' model of communicative competence. He also isolates several variables worthy of investigation, namely, the provision of gender judgments, accuracy, and certainty. He then reconceptualizes the problem of gender distinctiveness and impression formation in CIVIC by bridging the gap between textual markedness and expectations. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: Communicative competence; Computer-mediated communication; Electronic communications; Formal languages; Gender judgments; Linguistics; Problem solving; Research; dept.ils; peer-reviewed

Power information user model presents worthy premise but flawed methodology (multiple letters) - Iwema, C.L.; Sathe, N.; Lee, P.; Giuse, N. (Journal of the Medical Library Association, 2005)
Keywords: Community-Institutional Relations; Health Education; Humans; Inservice Training; Models, Organizational; Research Design; Tennessee; dept.ils; health care personnel; information dissemination; letter; library; library science; medical informatics; medical information system; methodology; public health; research; ⛔ No DOI found

Distance education and the new MLS: The employer's perspective - Kim, Hak Joon; Kusack, James Michael (Journal of Education for Library and Information Science, 2005)
Keywords: dept.ils

The present and future of China's National Science and Technology Library - A new paradigm of sci-tech information resource sharing - Meng, Liansheng; Liu, Yan Quan (New Library World, 2005)
Purpose - The purpose of this case study is to explore the construction pattern and issues involved with the development of the National Science and Technology Library (NSTL) in China. Design/methodology/approach - This study was conducted through an analytical evaluation of the historical development of scientific and technological information sharing among libraries and information centers and issues around construction of the NSTL. Findings - Since the establishment of its network service system at the end of 2000, the NSTL has made rapid progress in constructing a sci-tech information resource sharing system and offering web-based information services to the patrons of scientific and technical communities all over China. Originality/value - This paper is the first exploration that brings to the forefront the foundational background of the NSTL, the characteristics of its organizational structure, the functions of its service, and the tentative plan to increase its accessibility and usability. Symptomatic of the function of the NSTL constructing pattern will hopefully shed light not only to the reformation of the Chinese sci-tech information management system, but also to the development of scientific digital libraries in the world. © Emerald Group Publishing Limited.
Keywords: China; Digital libraries; Document management; Information services; National libraries; Worldwide web; dept.ils